Economy, Law, and Politics; Choudhury’s Theories and Fundamental Utopia - JM Muslimin (Jurnal Cita Hukum, 2020)
Abstracts Masudul Alam Choudhury agrees that fundamental thinking to construct a new knowledge base is needed when scientific and social conditions tend to be closed and monopolistic. The construction is expected to be able to dismantle the structural veil to find an alternative foundation and format that can be expected to realize social justice. For this reason, law, economics, and social paradigm can be effective instruments. In contrast to Choudhury, Karl Marx emphasized the existence of a new, rational-material awareness that dimensioned an economic struggle based on class consciousness, historical dialectics, and materialism as the choice of objectives above. This awareness can be grown contextually, by moving the oppressed to demand equality. So the legal, economic, and political foundations can change. While Choudhury focuses more on the transcendental dimension of the divine (tauhid paradigm) which is interpreted comprehensively and totally to dismantle the legal, economic, and social order. Thus, the legal, economic, and political infrastructure rests on fairness and productivity that remains competitive. The values that are in the divine foundation are arranged in the building of law and ethics (morals) to be integrated into the institution towards the desired reconstruction. However, Choudhury’s ideas remain normative and fail to be translated. It is too utopian. Keywords: historical-dialectical materialism, usury, exploitation, monotheism paradigm. AbstrakMasudul Alam Choudhury sependapat bahwa pemikiran fundamental untuk membangun basis pengetahuan baru diperlukan ketika kondisi ilmiah dan sosial cenderung tertutup dan monopolistik. Pembangunan tersebut diharapkan mampu membongkar kerudung struktural untuk menemukan alternatif pondasi dan format yang diharapkan dapat mewujudkan keadilan sosial. Oleh karena itu, paradigma hukum, ekonomi, dan sosial dapat menjadi instrumen yang efektif. Berbeda dengan Choudhury, Karl Marx lebih menekankan adanya kesadaran material rasional baru yang berdimensi perjuangan ekonomi berdasarkan kesadaran kelas, dialektika historis dan materialisme sebagai pilihan tujuan di atas. Kesadaran ini bisa ditumbuhkan secara kontekstual dengan menggerakkan kaum tertindas untuk menuntut kesetaraan. Jadi landasan hukum, ekonomi dan politik bisa berubah. Sedangkan Choudhury lebih menitikberatkan pada dimensi transendental ketuhanan (paradigma tauhid) yang dimaknai secara komprehensif dan menyeluruh untuk membongkar tatanan hukum, ekonomi dan sosial. Dengan demikian, infrastruktur hukum, ekonomi dan politik bertumpu pada keadilan dan produktivitas yang tetap kompetitif. Nilai-nilai yang ada dalam landasan ketuhanan ditata dalam bangunan hukum dan etika (akhlak) untuk diintegrasikan ke dalam institusi menuju rekonstruksi yang diinginkan. Namun, ide Choudhury tetap normatif dan gagal diterjemahkan. Itu terlalu utopis.Kata kunci: Materialisme Historis-Dialektik; Riba; Eksploitasi; Paradigma Tauhid АннотацияМасудул Алам Чоудхури согласен с тем, что фундаментальное мышление необходимо для создания новой базы знаний, когда научные и социальные условия имеют тенденцию быть закрытыми и монополистическими. Ожидается, что создание такой базы сможет демонтировать структурную завесу и найти альтернативные основы и форматы, которые, как ожидается, позволят реализовать социальную справедливость. Следовательно, правовая, экономическая и социальная парадигмы могут быть эффективными инструментами. В отличие от Чоудхури, Карл Маркс больше подчеркивал существование нового рационального материального сознания с измерениями экономической борьбы, основанными на классовом сознании, исторической диалектике и материализме как на выбранных выше целях. Это осознание можно усилить в контексте, мобилизуя угнетенных на требование равенства. Так что правовая, экономическая и политическая основы могут измениться. Между тем, Чоудхури больше сосредотачивается на трансцендентном измерении божественности (парадигма таухид – божественное единство), которая интерпретируется всесторонне и тщательно, чтобы разрушить правовой, экономический и социальный порядок. Таким образом, правовая, экономическая и политическая инфраструктура опирается на справедливость и производительность, которые остаются конкурентоспособными. Ценности, которые существуют в божественном основании, изложены в правовом и этическом (ахлакском) здании для интеграции в учреждения для желаемой реконструкции. Однако идеи Чоудхури оставались нормативными и не претворялись в жизнь. Это слишком утопично.Ключевые Слова: Историко-Диалектический Материализм; Ростовщичество; Эксплуатация; Парадигма Таухид